THE ROLE OF CHLOROPHYLL SPRAYING ACCORDING TO THE EVOLUTIONARY STANDARD ZADOKS IN THE GROWTH CHARACTERISTICS OF TWO CULTIVARS OF BREAD WHEAT - M. F. H. Al-Hassan; Hayder A. Baqir; J. W. Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A pilot study in the field was conducted within the study station of the Field Crops Department / College of Agricultural Engineering Sciences / “University of Baghdad during winter season of 2022-2023” .In order to find out the role of chlorophyll nutrient spraying on some growth traits of two varieties of bread wheat. Using RCBD design. The results showed a significant superiority of the V1 variety in all studied traits such as (Plant height measured in centimeters, number of tillers per square meter, and dry weight flowering100%, “the growth rate of the crop is g.m2.d-1, the hay yield in “ton .ha-1 biological yield ton. ha-1”, flag leaf area (cm2), chlorophyll concentration (SPAD), dry weight flag leaf g. , flag leaf’ specific gravity (g.), spike length (cm) which amounted to (100.04 cm, 281.34 g .m2.d-1, 242 .06 g.m2.d-1, 5.96 ton. ha, 11.79 ton .ha , 32.68 cm, 48.73 SPAD , 0.131 g. , 0.0039 g. and 12.13 cm). respectively . comparative V2 . chlorophyll nutrient concentrations showed that the level of Ch1 (1500) mg. L-1 represented a considerable improvement in most of which comprise the following attributes “plant height cm”, “number of tillers m2”, dry weight at flowering 100% g.m2, “crop growth rate g. m2.d-1, yield of straw ton. ha., The biological yield ton. ha., flag leaf area (cm), chlorophyll concentrations (SPAD) and spike length (cm) that reached (93.15 cm, 315.00 tillers m2, 257.08 g.m2, 1.904 g.m2, 5.96 ton. ha., 12.85 ton. ha. , 29.30 cm, and 12.07 cm) respectively, compared to the concentrations of Ch2 and Ch3.